Penerapan Model Adaptasi Roy dalam Praktik Residensi Keperawatan Medikal Bedah pada Pasien Kardiovaskular di RSJP Harapan Kita - Sofyan, Sofyan; Nurrachmah, Elly; Adam, Muhammad; Hidayat, Mukhlish (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Cardiovascular disease is one of the leading causes of death globally. Prevention and management efforts continue to be developed to address this issue. Specialist nurses play a role as direct care providers, applying evidence-based nursing and conducting nursing innovations. Specialized medical-surgical nursing residency programs have been implemented to apply the role of nurses as direct care providers, researchers, and innovators. The role of direct nursing care providers is carried out by providing nursing care to 30 cases managed through resumes and the primary case of Coronary Artery Disease 3VD using Roy's Adaptation Model theory. This study used a descriptive quantitative research design with a quasi-experimental approach. The sampling technique employed non-probability sampling using consecutive sampling, with 22 respondents selected as the sample for EBN implementation. The sampling technique utilized non-probability sampling with consecutive sampling. The number of respondents in the EBN application sample was 22, with univariate and bivariate analysis conducted. Statistical analysis results showed a significant difference in mean systolic and diastolic blood pressure between before and after the intervention (p=0.000). Practice analysis results indicated that the Roy Adaptation Model is effective for patients with cardiovascular system disorders.